Research was Carried Out to Evaluate the Various Factors Influencing the Survival Rate of Dental Implants - Ashfaque Ahmed Sahito, Mehar Ali, Syed Nasran Bibi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Dental implants had appeared to be the novel therapeutic strategy for vast popularity of respondents, and they are predicted to part in key role in oral restoration in future. The current research remained carried out to evaluate aspects that influence the rate of survival of dental implants. Methods: The latest research was carried out in Department of Endodontics. The above research included 5600 clients who had dental implants placed between March 2021 and Feb 2022 in Sir Ganga Ram Hospital, Lahore. Patients to hormonal imbalances, chronic contagious diseases, drug therapies, pregnant women, drug and alcohol addicts, and cases of severe chronic periodontitis have altogether been excepted. Name, oldness, sex, length, diameter, position, and bone quality remained one of the specifications recorded. IBM SPSS Statistics version 24.0, was used to tabulate and statistically significant analyze data. Results: There have been 2900 males and 2700 females among the 5600 patient populations. Maximum implant failures (56) were observed in patients over the age of 63 (males – 560, females –720). 22 ended in failure implants were found in the 42-year-old age category (males 760, females 570). There were 46 failed implants in the age group 42–61 years (males – 1600, females – 1270). The difference is not significant (P = 0.22). Implants with such a length of >12.6 mm (41/720) failed the most, accompanied by implants with either a length of 11 mm (23/1750) and 11–12.6 mm (65/2960). The distinction was statistically significant (P 0.06). Implants with just a diameter of 4.78 mm failed the most (40/1500), shadowed through implants having the width of >6.7 mm (17/1700) and implants with such the width of 4.78–5.6 mm (50/2600). The Chi-square test yielded statistically substantial (P 0.06). Mandibular posterior implants failed at 4.4 percent, maxillary posterior at 3.3 percent, maxillary anterior at 3.3 percent, and mandibular anterior at 2 percent; the current variance remained substantial (P 0.06). Type I bone had a 0.4 percent implant failure rate, Type II had the 1.96 percent disappointment degree, Type III had a 4 percent failure rate, and Type IV had a 0.9 percent failure rate; above distinction was substantial (P 0.06). Conclusion: The survival degree of implants is determined by variables just like age, implant measurement, radius, bone quality, but instead implant location. We discovered that implants greater than 12.6 mm in measurement and 4.76 mm diameter, placed in mandible posterior portion of Type III bone, had the highest failure rate.